2000
DOI: 10.1161/01.cir.102.9.1014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Long-Term Prognosis in Patients With Unstable Angina and Non–Q-Wave Myocardial Infarction

Abstract: Hospitalization for unstable angina or non-Q-wave myocardial infarction predicts a high 2-year morbidity and mortality; this is especially evident for patients with diabetes. Diabetic patients with no previous cardiovascular disease have the same long-term morbidity and mortality as nondiabetic patients with established cardiovascular disease after hospitalization for unstable coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
297
5
19

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(340 citation statements)
references
References 16 publications
19
297
5
19
Order By: Relevance
“…DM is associated with a higher incidence of myocardial infarction or cardiac death,2 and worse prognosis after ACS,37 percutaneous coronary intervention,38 and coronary artery bypass graft surgery 39. Panvascular inflammation in patients with DM presenting with ACS explains an increased risk for future nonculprit lesion‐related major adverse cardiovascular events in patients with DM 36.…”
Section: Discussionmentioning
confidence: 99%
“…DM is associated with a higher incidence of myocardial infarction or cardiac death,2 and worse prognosis after ACS,37 percutaneous coronary intervention,38 and coronary artery bypass graft surgery 39. Panvascular inflammation in patients with DM presenting with ACS explains an increased risk for future nonculprit lesion‐related major adverse cardiovascular events in patients with DM 36.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this fundamental step was the undisputed evidence that Type 2 diabetic subjects without a prior history of myocardial infarction (MI) have as a high risk of CHD as non-diabetic patients who have had a previous MI [4,5] as well as the extremely poor short-term prognosis of Type 2 diabetic subjects after their first MI [154,155]. ATP III and ADA guidelines identified LDL cholesterol as the first priority of lipid lowering and the optimal level was set <2.6 mmol/l [6,156].…”
Section: Consequences Of the Increase Of Vldl 1 Particlesmentioning
confidence: 99%
“…The International Diabetes Federation (IDF) foresees a rise of epidemic proportions in Type 2 diabetes that portends a daunting increase in CHD [3]. Solid evidence has confirmed that people with Type 2 diabetes have a similar risk of heart attack as people without diabetes who have already had a heart attack [4,5]. Adult Treatment panel III (ATP III) designated diabetes as a CHD risk equivalent and LDL was identified the first priority of lipid lowering [6].…”
mentioning
confidence: 99%
“…Previously, published studies showed that the cardiovascular prognosis of patients with diabetes without acute myocardial infarction (AMI) was similar to patients without diabetes but with a history of AMI (2)(3)(4). Consequently, the third National Cholesterol Education Program (NCEP) expert panel report on elevated blood cholesterol detection, assessment and treatment in adults (Adult Treatment Panel III -ATP III), considered the patient with diabetes as "coronary equivalent" (5).…”
Section: Introductionmentioning
confidence: 99%